Introduction to nuclear science - Bryan, Jeff C.
"This introductory textbook covers general aspects of nuclear chemistry and physics. It discusses how nuclear science impacts our daily lives through medicine, electrical power generation, food safety, waste, and weapons. This second edition features four new chapters that address nuclear reactors, dosimetry, radiochemistry, and nuclear forensics. It also expands coverage of nuclear medicine and radiation therapy. With additional end-of-chapter problems, the text provides critical information for students earning nuclear-related degrees in the coming years, as well as providing an accessible reference for anyone with some post-secondary education and an interest in nuclear issues"--